Development of absorptive capacity in a regional innovation system: experience of Lithuanian regions - Juknevičienė, Vita (Journal of Education Culture and Society, 2020)
The importance of innovativeness and competitiveness is rising and it is the essential condition for the survival in a global market. Especially it is vitally important for small countries (and their regions), which do not have the exceptional situation and position in the market, acknowledged products (services) or resources, even stable long-term traditions of innovation culture, etc. The present paper focuses on absorptive capacity, its development issues in regional innovation systems and well-being creation in a small country’s regions. For the purposes of the research, analyses were carried out, identifying reasons (or barriers), promoting (or limiting) innovative activities, impeding organizational propensities and desire to develop activities of knowledge access, anchoring and diffusion at the organizational and inter-organizational level. This paper reveals the experience of Lithuanian regions from the point of view of experts, representing institutions of science, business, innovation and business support. This paper represents the experience of partnerships (successful and failed) for the knowledge absorption in Lithuania and their connection to subsequent directions of organizational behavior and decisions. Furthermore, the author suggests main aspects for managers, seeking to maintain (gain) organizational absorptive capacity, corresponding to requirements and speed of the modern market.